Effect of Laser on the Bound Magnetic Polaron in a Semimagnetic Quantum Wire - C. Raja Mohan; K. Jayakumar (Журнал нано- та електронної фізики)
In the present investigation binding energy of the laser dressed hydrogenic donor in a Semi magnetic Quantum Wire like Cd1 – xMnx2Te/Cd1 – x1Mnx1Te/Cd1 – x2Mnx2Te and spin polaronic shift has been computed for various magnetic and laser fields within the effective mass approximation in the finite barrier model using variational method. The results are presented and discussed.